(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the potential of artificial intelligence (AI) in the process of foreign language teaching. Compared with traditional methods of learning and teaching foreign languages, the advantages of artificial intelligence technologies, including efficiency in language learning, individual approach and flexibility, are discussed. The article also discusses the potential of artificial intelligence-based educational platforms, the main problems in language learning and the role of artificial intelligence in overcoming them.